Developmental trauma, complex PTSD, and the current proposal of DSM-5 - Sar, Vedat (Co-Action Publishing, 2011)

(untitled)
This paper evaluates representation of clinical consequences of developmental psychological trauma in the current proposal of DSM-5. Despite intensive efforts by its proponents for two decades, it is not known yet if Complex PTSD will take a place in the final version of DSM-5. Recognition of dissociative character of several symptom dimensions and introduction of items about negative affects such as shame and guilt imply an indirect improvement toward better coverage of the consequences of developmental trauma in the existing category of PTSD. As disorders with highest prevalence of chronic traumatization in early years of life, dissociative disorders and personality disorder of borderline type are maintained as DSM-5 categories; however, recognition of a separate type of trauma-related personality disorder is unlikely. While a preschooler age variant of PTSD is under consideration, the proposed diagnosis of Developmental Trauma Disorder (child version of Complex PTSD) has not secured a place in the DSM-5 yet. We welcome considerations of subsuming Adjustment Disorders, Acute Stress Disorder, PTSD, and Dissociative Disorders under one rubric, i.e., Section of Trauma, Stress, or Event Related Disorders. Given the current conceptualization of DSM-5, this paper proposes Complex PTSD to be a subtype of the DSM-5 PTSD. Composition of a trauma-related disorders section would facilitate integration of knowledge and expertise about interrelated and overlapping consequences of trauma.